Analysis of Students' Ability to Work on Higher Order Thinking Skillsin Thematic Science Learning - Rahmadhani, Putri; Wirayuda, Ricky Purnama (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to look at students' abilities in working on HOTS (Higher Order Thinking Skills) questions in science learning at Madrasah Ibtidaiyah Al-Hidayah Kebon IX Muaro Jambi Methodology: This study uses a quantitative descriptive research design. The population of this study was class V Madrasah Ibtidaiyah Al-Hidayah Kebon IX, which consisted of 2 classes, namely class VA and class VB. The total population in this study is 38 students. From the entire population, 22 VA class students were selected as a sample. The sampling technique used in this study was purposive sampling which, based on criteria had applied HOTS (Higher Order Thinking Skills) questions to science learning. Main Findings: The ability of Madrasah Ibtidaiyah Al-Hidayah Kebon IX students in working on Higher Order Thinking Skills questions in science learning is in a fairly good category. Novelty/Originality of this study: With this research, it can be useful for teachers to find out how far students' abilities are in working on Higher Order Thinking Skills questions, especially in learning mathematics and teachers can also improve students' abilities to work on Higher Order Thinking Skills questions which are at the level of analyzing, evaluating, and creating.